Does the Implementation of a National Health Insurance Program Result in Rationing Care for Ischemic Stroke Management? Analysis of the Indonesian National Health Insurance Program - Amalia L (Dove Medical Press, 2023)
Lisda Amalia Department of Neurology, Faculty of Medicine, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Lisda Amalia, Department of Neurology, Faculty of Medicine, Universitas Padjadjaran, Jl. Eykman 38, Bandung, 40161, Indonesia, Email dr.lisda@gmail.comBackground: There are 2.2 million stroke patients in Indonesia, and ischemic stroke represents 87% of all strokes. Ischemic stroke is one of the covered diseases (INA-CBGs) in the National Health Insurance (JKN). Based on the Indonesian Ministry of Health's data, stroke uses up 1% of the yearly budget. This study compares clinical outcomes and treatment patterns before and during the JKN era.Methods: A cross-sectional analytical study of ischemic stroke medical records treated at Hasan Sadikin Hospital in 2013 and 2015 as representatives of the before and during JKN era. Chi-Square is used for data processing relationship analysis.Results: 164 ischemic stroke patients were treated, 75 before implementing the JKN program and 89 after implementing the JKN program. There was a significant difference between treatment patterns (p< 0.001) and clinical outcomes (p=0.046) of ischemic stroke patients before and after implementing The Indonesian National Health Insurance. There was no significant difference in length of stay (LOS).Conclusion: There is significant different between treatment pattern and clinical outcome of ischemic stroke patients before and after implementing The Indonesian National Health Insurance. This program has improved clinical outcomes concerning the purpose of the JKN program to provide social protection and welfare in terms of health.Keywords: ischemic stroke, treatment pattern, national health insurance, clinical outcome